A theoretical catalytic mechanism for methanol reforming in CeO2 vs Ni/ CeO2 by energy transition states profiles - Reyna Alvarado, Jorge; Ramos Murillo, Manuel Antonio; Pérez-Hernández, Raúl; José, Rodríguez (2021)
We present a theoretical study using Halgren-Lipscomb algorithm assisted by DFT + U to determine the catalytic mechanism for hydrogen production by steam reforming of methanol over CeO2 and Ni/CeO2 model catalytic surfaces. Our main goal is to describe the physical-chemical interaction between nickel with CeO2 matrix support and catalytic conversion mechanism in response to experimental evidence. The results from transition energy states in (111) and (111) CeO2 surfaces, with and without nickel cluster, indicate that process is favored when metallic nickel is contained, however, exothermic energies in bare CeO2 supports prior suggestions ascribing the particular catalytic activity enhancement of Ni/CeO2 nanorod for methanol steam reforming due a synergistic effect of the CeO2 exposed planes of the nanorods and Ni clusters. Our aim is to provide key data for the improvement and enhancement, in terms of efficiency and viability, the current production of hydrogen by methanol steam reforming by Ni/CeO2 systems.